2008
DOI: 10.1136/jme.2007.022772
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ attitudes towards “do not attempt resuscitation” status

Abstract: This study suggests that contrary to current practice most patients want to discuss their DNAR status prior to becoming critically ill. This includes half of the small number that find it distressing to discuss. Although most patients are comfortable with relatives being involved in discussing DNAR, a significant proportion do not want their relatives to be asked. Furthermore, once a decision has been made, the majority of patients want it to be more accessible than current practice allows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 7 publications
1
33
0
2
Order By: Relevance
“…DNAR-Entscheidungen und zu DNAR gehörige Besprechungen sollen klar in der Akte des Patienten aufgezeichnet werden [1001][1002][1003][1004]. Mit der Zeit kön-nen sich die Situation oder die Ansichten des Patienten ändern, sodass DNAR-Anweisungen entsprechend überprüft werden sollen [1005].…”
Section: Anwesenheit Der Familie Während Der Reanimationunclassified
“…DNAR-Entscheidungen und zu DNAR gehörige Besprechungen sollen klar in der Akte des Patienten aufgezeichnet werden [1001][1002][1003][1004]. Mit der Zeit kön-nen sich die Situation oder die Ansichten des Patienten ändern, sodass DNAR-Anweisungen entsprechend überprüft werden sollen [1005].…”
Section: Anwesenheit Der Familie Während Der Reanimationunclassified
“…However, even if a patient has a poor prognosis, it does not always mean that he/she does not wish to be resuscitated or receive aggressive treatment. As the final decision on DNAR orders will differ according to the attitude of the individual patient,10, 11, 12, 13 it is essential to confirm each and every patient's intentions wherever possible. Apart from these diseases and background factors, patients with sequelae of cerebrovascular disease or dementia or patients in a persistent vegetative state may lack decision‐making capability.…”
Section: Discussionmentioning
confidence: 99%
“…With reference to timing, there were indications that screening should take place prior to hospital admission [33], however in reality, the literature indicated that screening is mostly conducted on admission or post admission (within 3 days) [5,28]. Reviewed articles noted that for many patients, emotional, psychological and practical concerns are particularly pronounced on admission [32], however the pre-surgical processes and procedures rarely accommodate such screening or responses to these concerns [27].…”
Section: Psychosocial Screeningmentioning
confidence: 99%